UMPSA provides ready-to-eat express meal for undergrads - T.N., Alagesh (New Straits Times Press (M) Bhd., 2025)
KUANTAN: Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has introduced its in-campus retort food, or pre-packed meals, to ensure no student goes hungry.